2017
DOI: 10.1007/s41669-017-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health Status of Type 2 Diabetes Outpatients Receiving Care in a Tertiary Hospital in Nigeria

Abstract: ObjectivesThe aim of this study was to determine the health status of type 2 diabetes patients in a Nigerian tertiary hospital, and examine the sociodemographic and clinical variables that predicted the health status of type 2 diabetes patients in terms of utility valuations and EuroQol Visual Analogue Scale (EQ-VAS) score.MethodsThis was a cross-sectional study of 147 diabetes patients attending the University of Nigeria Teaching Hospital, Enugu State, Nigeria. The EQ-5D-5L instrument, version 2.1, was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
6
12
0
Order By: Relevance
“…20 Still, equal health status was independently documented in recent Nigerian studies employing the EQ-5D instrument among patients with type II diabetes. 29,33 This observation indicates that in Nigeria, HIVinfected patients value their health state similar to that of type II diabetes patients. Also, our finding was identical to the health valuations of the Zimbabwean general population (mean EQ-VAS = 79.8), whose country-specific utility weight we adopted in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…20 Still, equal health status was independently documented in recent Nigerian studies employing the EQ-5D instrument among patients with type II diabetes. 29,33 This observation indicates that in Nigeria, HIVinfected patients value their health state similar to that of type II diabetes patients. Also, our finding was identical to the health valuations of the Zimbabwean general population (mean EQ-VAS = 79.8), whose country-specific utility weight we adopted in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…For patients with diabetes mellitus (Table 2), 12 studies reported health utility values ranging from 0.31 to 0.99 (14,15,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The Chinese standard EQ-5D-5L value set (18) and Crosswalk UK value set (24) were used to derive the utility values in the studies that reported the highest value and lowest value, respectively.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…The results showed that the utility value calculated with the Uruguay value set was the highest at 0.880, while the lowest, 0.735, was derived with the value set from the Netherlands. The EQ-5D VAS scores were reported to range from 50.9 to 72.6 in six studies (14,20,(22)(23)(24)(25). Among the five dimensions of the EQ-5D-5L, pain/discomfort was the dimension with the most reported problems.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Typically though, the awareness of diabetes among patients remains a major challenge in SSA with only a minority of patients currently aware of their diabetic status and being actively treated, with only a small percentage being diagnosed pre-diabetes (Zekewos et al, 2018;Manne-Goehler et al, 2019). This needs to be urgently addressed given the morbidity, mortality, and costs associated with diabetes (Glover et al, 2012;Glezeva et al, 2015;Low Wang et al, 2016;Atun et al, 2017;Adibe et al, 2018;Lewis et al, 2018;Pheiffer et al, 2018;Rwegerera et al, 2018;Mapa-Tassou et al, 2019). Eighty percent of early deaths due to non-communicable diseases (NCDs) including diabetes and cardiovascular diseases (CVD) currently occur in lower and middle income countries (LMICs), with the morbidity and mortality of diabetes and other NCDs such as CVD likely to be greater than communicable disease by 2025 (Peer et al, 2014;Renzaho, 2015;Issaka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa for instance as a result of changes in peoples' diet and lifestyle, diabetes has moved from being the fifth leading underlying cause of death in 2013 to now the second most common cause, representing 5.5% of all recorded deaths (Statistics South Africa, 2016;Moosa et al, 2019). T2DM also results in a lower health status and quality of life (Fasanmade and Dagogo-Jack, 2015;da Mata et al, 2016;Adibe et al, 2018;Rwegerera et al, 2018), with high rates of sight threatening retinopathy among diabetic patients in Africa (Glover et al, 2012;Jingi et al, 2015;Cairncross et al, 2017;Pastakia et al, 2017;Lewis et al, 2018) as well as nephropathy (Thomas et al, 2016;Wagnew et al, 2018) and neuropathy (Awadalla et al, 2017;Sun et al, 2020). Overall, populations of African origin appear to have the highest prevalence of microvascular complications of diabetes exacerbated by frequent high blood pressure and inappropriate diabetes control among the diabetes population along with challenges of access to appropriate care (Mbanya and Sobngwi, 2003;Mbanya et al, 2010).…”
Section: Introductionmentioning
confidence: 99%